The role of the preparatory training program proposed by the Ministry of Education in improving the competence of new physical education and sports teachers for the intermediate level. - hadji, Abdelkader (sports creativity, 2025)
The current study aims to identify the extent to which the preparatory training program contributes to providing new physical education teachers with cognitive competencies as to prepare them to be qualified teachers, and if the content of this training program provides teachers with opportunities for training in how to plan and implement as well as evaluate the physical education and sports study. The study also aims to know the extent of the effectiveness of the preparatory training program in preparing teachers of physical education and sports as required and desired.The sample included: 12 teachers of physical education and sports who succeeded in the employment competition on the basis of the certificate, chosen in an intended manner, as the researcher relied on the descriptive approach, and used the questionnaire as a tool to collect data. The data was processed statistically using percentage form, as the results showed that the training program focused on raising the capabilities of the trainee teachers in the implementation and application of the lesson, in order to achieve the goals established in the national education curricula, and did not focus sufficiently on the process of training new teachers to raise the efficiency of lesson planning and evaluation, and this is due to the nature of the school subjects in the preparatory training program asteachers of physical education and sports, which neglected that the subject of physical education and sports emphasizes practicing field operationsrather than the theoretical side, as is the case of this program.